A cytomegalovirus induced cavitary pneumonia case in a patient with idiopathic thrombocytopenic purpura under corticosteroid treatment - İncaman, Deniz; Çınar, Mahmut (Lycia Press London UK, 2022)
Objective: Cytomegalovirus infection is common in the neonatal period, during childhood, while in adults, it is encountered in immunosuppressed patients. CMV infection is a serious cause of mortality. CMV pneumonitis is seen most frequently in adults, even if ganciclovir treatment is given prophylactically after stem cell transplantation and it is seen at least after kidney transplantation. In this article, we present a case of severe cavitary pneumonia that develops in a patient with prolonged prednisolone therapy due to ITP.
Keywords: 3. Good health